Gut microbiome in gastrointestinal neoplasms: from mechanisms to precision therapeutic strategies - Song, Jiaqian; Zhang, Wei; Wang, Deqiang (Gut pathogens, 2025)
The incidence of Gastrointestinal Neoplasms (GI neoplasms) continues to increase globally. Colorectal cancer (CRC), in particular, has emerged as the second leading cause of cancer-related mortality worldwide. Now, Specific pathogenic bacteria, such as Fusobacterium nucleatum (F. nucleatum) and Helicobacter pylori (H. pylori), critically promote tumorigenesis through multiple mechanisms, including the induction of genotoxic damage, host metabolic reprogramming, and remodeling of the tumor immune microenvironment. Notably, a dysbiotic Gut Microbiome (GM) state significantly compromises patient response rates to cancer therapeutics. This review aims to systematically analyze the core molecular mechanism of GM affecting tumor development and explore the precise intervention strategies guided by clinical translation. This systematic review adhered to the PRISMA-2020 guidelines. We conducted a comprehensive literature search in PubMed (2008-2025) using key terms including "Gut Microbiome", "Gastrointestinal Neoplasms", "Fecal Microbiota Transplantation (FMT)", "immunotherapy resistance", "precision-based interventions", and "emerging research frontiers". Preclinical and clinical studies investigating the mechanisms, diagnostic applications, and therapeutic interventions of the GM in GI neoplasms were included. This review systematically elucidates the tripartite mechanisms by which the GM influences the initiation and progression of GI neoplasms. And we innovatively proposed the "Proinflammation-metabolism-Immune framework (Dysbiosis of the GM jointly leads to the occurrence, development and metastasis of GI neoplasms by driving three interrelated processes: chronic inflammation (Proinflammation), reshaping the Metabolism of the host and TME(Metabolism), and inhibiting or altering the host Immune surveillance (Immune))" To deepen the understanding of host-microbe interactions. Based on this framework, we focused on discussing the therapeutic strategy targeting GM and confirmed its significant impact on the efficacy of anti-cancer treatment. Although these strategies have demonstrated clinical potential, current research is still mainly confined to preclinical models and the early clinical trial stage. To address this, we outline future directions: Integrating emerging technologies like multi-omics and artificial intelligence will enable dynamic monitoring and real-time modulation of microbial activity. This integration aims to establish a novel paradigm for microbiome-based personalized precision medicine. This review systematically clarifies that GM is a key target for optimizing the treatment of GI neoplasms. Future research should integrate multi-omics and AI technologies for dynamic microbial monitoring and modulation, paving the way for microbiome-based precision medicine. Overcoming challenges in standardization and clinical translation is essential.